Chemical Quality Analysis of Meal Quail Meat with Rations Containing Fermented Bean Sprouts Waste Flour: - - Seri Rejeki I Gusti Ayu Dewi; Ni Ketut Mardewi; Ni Ketut Sri Rukmini; A.A.S. Putri Risa Andriani; S.A.M.P. Suryani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Quail is one of the poultry that has the potential to be developed as a source of diversification for meat and egg products. Bean sprouts have high levels of crude protein and crude fiber, so fermentation is necessary. The amount of ration costs range from 60-80% of all production costs. This study aims to determine the chemical quality of male quail meat given rations containing fermented bean sprout waste and to compare the various levels of bean sprout flour in the ration to the chemical quality of male quail meat. This research was conducted using a completely randomized design (CRD) with 4 treatments and 4 replications for each treatment. The treatments consisted of rations without the addition of fermented bean sprouts waste flour (TLTF) (P0), rations with 5% TLTF (P1), rations with 10% TLTF (P2), and rations with 15% TLTF (P3). The variables analyzed were water content, ash content, crude fat, and pH. The results of this study indicate that the provision of rations containing fermented bean sprout waste does not affect the quality of male quail meat.